Human Papillomavirus Vaccination in South Africa: Programmatic Challenges and Opportunities for Integration With Other Adolescent Health Services? - Amponsah-Dacosta, Edina; Blose, Ntombifuthi; Nkwinika, Varsetile Varster; Chepkurui, Viola (Frontiers in Public Health, 2022)
Compared to other regions of the world, sub-Saharan Africa has made limited progress in the implementation and performance of nationwide human papillomavirus (HPV) vaccination programmes. Without urgent intervention, this will serve to undermine cervical cancer elimination efforts in this region. The primary intent of this narrative review is to highlight the programmatic successes and challenges of the school-based HPV vaccination programme in South Africa since its inception in 2014, with the aim of contributing to the evidence base needed to accelerate implementation and improve programme performance in other sub-Saharan African countries. As of 2020, the proportion of adolescent girls aged 15 years who had received at least one dose of the HPV vaccine at any time between ages 9 – 14 years was 75%, while 61% had completed the full recommended two-dose schedule. This gives some indication of the reach of the South African HPV vaccination programme over the past six years. Despite this, vaccine coverage and dose completion rates have persistently followed a downward trend, slowing progress towards attaining global elimination targets. There is evidence suggesting that declining public demand for the HPV vaccine may be a result of weakening social mobilization over time, inadequate reminder and tracking systems, and vaccine hesitancy. Another concern is the disproportionate burden of HPV and HIV co-infections among adolescent girls and young women in South Africa, which predisposes them to early development of invasive cervical cancer. Moving forward, national policy makers and implementers will have to explore reforms to current age eligibility criteria and vaccine dose schedules, as well as implement strategies to support vaccine uptake among populations like out-of-school girls, girls attending private schools, and HIV positive young women. Additional opportunities to strengthen the South African HPV vaccination programme can be achieved by scaling up the co-delivery of other adolescent health services such as comprehensive sexual and reproductive health and rights education, deworming, and health screening. This calls for reinforcing implementation of the integrated school health policy and leveraging existing adolescent health programmes and initiatives in South Africa. Ultimately, establishing tailored, adolescent-centered, integrated health programmes will require guidance from further operational research.